Pengaruh Kepercayaan Wajib Pajak, Transparansi Pajak, dan Efektivitas Sistem Perpajakan terhadap Kepatuhan Wajib Pajak Orang Pribadi - Fitri Erliya Wati; Hero Priono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to examine how individual taxpayer compliance is influenced by taxpayer trust, tax transparency, and system efficiency at KPP Pratama Surabaya Sukomanunggal. The research uses a quantitative approach with an explanatory method, involving 100 non-employee individual taxpayers selected using the accidental sampling technique. A sample of 100 taxpayers with a 10% margin of error was selected using Slovin's methodology. A Likert scale questionnaire is one tool used to gather data, while SmartPLS 4.0 software is used to evaluate the results using the PLS-SEM approach. The results of the study show that tax openness and the efficiency of the tax system have a positive and large influence on taxpayer compliance, whereas taxpayer trust has a positive but negligible effect. These findings indicate that system factors and information transparency are more dominant in influencing compliance compared to perceptions of institutions.